2014
DOI: 10.1051/0004-6361/201424172
|View full text |Cite
|
Sign up to set email alerts
|

HIP 114328: a new refractory-poor and Li-poor solar twin

Abstract: Context. The standard solar model fails to predict the very low lithium abundance in the Sun, which is much lower than the proto-solar nebula (as measured in meteorites). This Li problem has been debated for decades, and it has been ascribed either to planet formation or to secular stellar depletion due to additional mixing below the convection zone, either during the pre-main sequence and thus possibly linked to planet formation, or additionally on secular time-scales during the main sequence. In order to tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 49 publications
7
47
2
17
Order By: Relevance
“…Our analysis revealed that the Be abundance is relatively constant with age, with a scatter of only 0.04 dex and a weak, if any, trend with age. This is in contrast to the large observed depletion of Li with age (Baumann et al 2010;Monroe et al 2013;Meléndez et al 2014b), showing that the transport mechanisms are deep enough to reach the region where Li is burned, but not deep enough to reach the higher temperatures needed to burn Be. Our Li and Be results provide stringent constraints on stellar models and nonstandard mixing processes beyond treating convection through the mixing length theory.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our analysis revealed that the Be abundance is relatively constant with age, with a scatter of only 0.04 dex and a weak, if any, trend with age. This is in contrast to the large observed depletion of Li with age (Baumann et al 2010;Monroe et al 2013;Meléndez et al 2014b), showing that the transport mechanisms are deep enough to reach the region where Li is burned, but not deep enough to reach the higher temperatures needed to burn Be. Our Li and Be results provide stringent constraints on stellar models and nonstandard mixing processes beyond treating convection through the mixing length theory.…”
Section: Discussioncontrasting
confidence: 56%
“…The importance of solar twins is that as they Article published by EDP Sciences L10, page 1 of 4 have nearly solar mass and composition (Meléndez et al 2014b), their evolution is similar to that of the Sun. Hence, solar twins at different evolutionary stages in the main sequence can be used as proxies of the Sun at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Severe Li depletion is also observed; this is a sign of old age (Monroe et al 2013;Meléndez et al 2014a) that also contradicts the young age scenario. When the phenomenon occurs through mass-transfer events (i.e., a mass exchange between a now "dead" star during its AGB phase, which pollutes its companion's photosphere, in the process also transferring angular momentum; McCrea 1964), enhancement of s-process elements is predicted for a sufficiently massive AGB donor, as well as abundance anomalies of light elements (Desidera et al 2007).…”
Section: Introductionmentioning
confidence: 89%
“…The observations for this sample are described in Meléndez et al (2014a). To summarise them briefly, we observed with UVES at the VLT in dichroic mode, with the 346 nm setting (306−387 nm) in the blue arm and the 580 nm setting (480−682 nm) in the red arm.…”
Section: Observationsmentioning
confidence: 99%
“…We estimate that the rate of lithium depletion is too small in the Sun and that this therefore favours the early depletion scenario. (Meléndez et al 2014). Grey and unfilled circles and triangles are twins from (Carlos et al 2016); triangles are the upper limits on lithium abundance; three unfilled circles are twins-exceptions which can be interpreted in the framework of the early depletion scenario.…”
Section: Solar Twinsmentioning
confidence: 99%